Evaluasi Implementasi Program Jamsostek Tenaga Kerja Luar Hubungan Kerja (TK-LHK) Sektor Informal Di Kota Semarang - Nuki M N; Suwanto Adhi; Lusia Astrika (Journal of Politic and Government Studies, 2013)
The theory used in this study include: Policy Evaluation, Policy Implementation and Informal Sector. The purpose of this study was to evaluate how the implementation of the Jamsostek program and to find out the factors that influence the Jamsostek TK-LHK program at Semarang city. This research method is descriptive qualitative. This study uses an open interview in which the subject knew that they were being interviewed and also know what the purpose of the interview. Sampling was purposive sampling by a new president for the association or group deemed to know information about the program.These results indicate that the evaluation of the implementation Jamsostek program TK-LHK Informal Sector at Semarang city has not managed in accordance with the objectives and targets achievement. The assessment can be described by seven indicators of evaluation all indicators are still not fill full. Factors that hinder the program is also evident from the lack of knowledge about the target group of this program. As for the factors supporting this program lies in the consciousness of society are aware of the importance of socio-economic security for them as well as the support from the community to help spread the program to other communities in particular are being targeted. Keywords: Evaluation, Implementation, Jamsostek TK-LHK and the Informal Sector